Agri-Business Incubation for Small-holder Plantation Crops - Muralidharan, K; Jayasekhar, S (Indian Farming, 2020)
Coconut, arecanut and cocoa are the important small-holder plantation crops of India which exert profound influence on the rural economy by supporting the livelihoods of 25 million people in the country. They also support the national agrarian economy, with annual contribution to the tune of ` 14,200 crores to the national GDP and foreign exchange earnings of about ` 2,440 crore, besides supporting subsidiary industrial development. Owing to traditional methods of processing and product utilization, the sector is alien to modernization which hampers sector’s vertical growth. This leads to greater price instability and lesser input use efficiency, which is felt more after global integration in the post World Trade Agreement (WTA) and ASEAN treaty era. To ensure the livelihood security of those dependent on the small-holder plantation crops, it is of paramount importance to strengthen the commodity value chains through appropriate forward and backward integration. Keeping abreast of the race in productivity alone cannot guarantee success or even survival in an activity exposed to unmediated global competition. It is, thus, imperative to think beyond the periphery of production and productivity and there lies the importance of technology driven agri-business initiatives.